Development of a new model for evaluating malaria risk In Chimoio, Mozambique - Gouveia, Sofia Damiana Vieira da Luz (2021)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Knowledge Management and Business Intelligence